Advanced Oxidation Protein Products and Carbonylated Proteins as Biomarkers of Oxidative Stress in Selected Atherosclerosis-Mediated Diseases. (13th August 2017) - Gryszczyńska, Bogna; Formanowicz, Dorota; Budzyń, Magdalena; Wanic-Kossowska, Maria; Pawliczak, Elżbieta; Formanowicz, Piotr; Majewski, Wacław; Strzyżewski, Krzysztof Wojciech; Kasprzak, Magdalena P.; Iskra, Maria
Abstract : Objectives . The main question of this study was to evaluate the intensity of oxidative protein modification shown as advanced oxidation protein products (AOPP) and carbonylated proteins, expressed as protein carbonyl content (C=O) in abdominal aortic aneurysms (AAA), aortoiliac occlusive disease (AIOD), and chronic kidney disease (CKD). Design and Methods . The study was carried out in a group of 35 AAA patients and 13 AIOD patients. However, CKD patients were divided into two groups: predialysis (PRE) included 50 patients or hemodialysis (HD) consisted of 34 patients. AOPP and C=O were measured using colorimetric assay kit, while C-reactive protein concentration was measured by high-sensitivity assay (hsCRP). Results . The concentration of AOPP in both AAA and AIOD groups was higher than in PRE and HD groups according to descending order: AAA~AIOD > HD > PRE. The content of C=O was higher in the PRE group in comparison to AIOD and AAA according to the descending order: PRE~HD > AAA~AIOD. Conclusions . AAA, AIOD, and CKD-related atherosclerosis (PRE and HD) contribute to the changes in the formation of AOPP and C=O. They may promote modification of proteins in a different way, probably due to the various factors that influence oxidative stress here.